Botulinum Neurotoxin Detection Methods for Public Health Response and Surveillance - Thirunavukkarasu, Nagarajan; Johnson, Eric; Pillai, Segaran; Hodge, David; Stanker, Larry; Wentz, Travis; Singh, BalRam; Venkateswaran, Kodumudi; McNutt, Patrick; Adler, Michael; Brown, Eric; Hammack, Thomas; et al. (Frontiers in Bioengineering and Biotechnology, 2018)
Botulism outbreak due to consumption of food contaminated with botulinum neurotoxins (BoNTs) is a public health emergency. A single suspected case of foodborne botulism caused by food contaminated with botulinum neurotoxin (BoNTs) could evoke public health emergency. The threat of bioterrorism through deliberate distribution in food sources and/or aerosolization of BoNTs raises global public health and security concerns due to the potential for high mortality and morbidity. Rapid and reliable detection methods are necessary to support clinical diagnosis and surveillance for identifying the source of contamination, performing epidemiological analysis of the outbreak, preventing and responding to botulism outbreaks. This review considers the applicability of various BoNT detection methods and examines their fitness-for-purpose in safeguarding the public health and security goals.